1990
DOI: 10.1200/jco.1990.8.4.576
|View full text |Cite
|
Sign up to set email alerts
|

The treatment of recurrent brain metastases with stereotactic radiosurgery.

Abstract: Between May 1986 and August 1989, we treated 18 patients with 21 recurrent or persistent brain metastases with stereotactic radiosurgery using a modified linear accelerator. To be eligible for radiosurgery, patients had to have a performance status of greater than or equal to 70% and have no evidence of (or stable) systemic disease. All but one patient had received prior radiotherapy, and were treated with stereotactic radiosurgery at the time of recurrence. Polar lesions were treated only if the patient had u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
0
2

Year Published

1996
1996
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(86 citation statements)
references
References 6 publications
2
82
0
2
Order By: Relevance
“…) of R3616 or buffer with a Hamilton syringe; (3) mice subjected to ionizing radiation and either not injected or injected with buffer solution; and (4) control mice or mice administered R3616 and subjected to irradiation for 20 Gy at 1 day after infection or mock infection and with 25 Gy at 2 days after infection or mock infection. Although large for conventional clinical radiation fractionation protocols, fraction sizes of 20-25 Gy are employed in stereotactic radiosurgery [17][18][19] and preliminary experiments suggest that smaller radiation doses will also be effective. The tumor mass was measured biweekly for 60 days or at least until the tumor mass reached 2000 mm 3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…) of R3616 or buffer with a Hamilton syringe; (3) mice subjected to ionizing radiation and either not injected or injected with buffer solution; and (4) control mice or mice administered R3616 and subjected to irradiation for 20 Gy at 1 day after infection or mock infection and with 25 Gy at 2 days after infection or mock infection. Although large for conventional clinical radiation fractionation protocols, fraction sizes of 20-25 Gy are employed in stereotactic radiosurgery [17][18][19] and preliminary experiments suggest that smaller radiation doses will also be effective. The tumor mass was measured biweekly for 60 days or at least until the tumor mass reached 2000 mm 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Although large for conventional clinical radiation fractionation protocols, fraction sizes of 20-25 Gy are employed in stereotactic radiosurgery. [17][18][19] The tumor mass was measured biweekly for 60 days or at least until the tumor mass reached 2000 mm 3 . Tumor volumes were calculated using the formula (length × width × height)/2 which is derived from the formula for an ellipsoid ( d 3 )/6.…”
Section: Cells and Virusesmentioning
confidence: 99%
“…Radiosurgery has been reported in the treatment of many different intracranial lesions, both benign and malignant, and is widely accepted as safe and effective. 5,9,20,27,28,34 Stereotactic radiosurgery offers a method for delivering high-dose radiation in a single or limited number of fractions to a small volume encompassing the tumor while minimizing the dose to adjacent normal structures. The authors of a study originating from the University of Arizona in 1996 demonstrated that spinal stereotactic radiosurgery involving the use of a body frame was both feasible and safe.…”
Section: Discussionmentioning
confidence: 99%
“…Radiosurgery has been used to treat many different intracranial lesions, both benign and malignant, and is widely accepted as both safe and effective. 4,6,18,24,25,29 There is reason to believe that radiosurgery in which similar doses are used would be equally efficacious in the treatment of sacral lesions.…”
Section: Neurosurg Focus / Volume 15 / August 2003mentioning
confidence: 99%